Development of Direct Drive Bogies with Permanent Magnet Motors at Home and Abroad - Xiongfei ZHANG (机车电传动)
This paper introduced the development of direct drive bogies and direct drive technology with permanent magnet motors at home and abroad, and analyzed the advantages and disadvantages of direct drive technology of bogies and its future development trend, which provided reference for the development of direct drive bogies for our country.